Literature Review Penggunaan Teknologi Kecerdasan Buatan dalam Penerbangan: Analisis Perkembangan Teknologi, Potensi Keamanan, dan Tantangan - Biringkanae, Pipa; Bunahri, Rifqi Raza (Dinasti Review Publisher, 2023)
This literature review examines the development and potential of Artificial Intelligence (AI) in aviation, particularly in aircraft design, air traffic control, and maintenance. AI has the potential to revolutionize the industry by making aircrafts more efficient, lighter, and safer. The use of AI in air traffic control can also reduce delays and improve safety. One of the most significant potential benefits of AI in aviation is increased security, as it can be used to detect potential security threats and prevent hijackings or other security breaches. However, the implementation of AI in aviation also presents challenges such as significant investment in infrastructure and training, concerns about job loss, and ensuring the security and privacy of data. Despite these challenges, the potential benefits of AI in aviation make it a promising field of development for the industry.